Encountering Settler Colonialism Through Legal Objects: A Painted Drum And Handwritten Treaty From Manitoulin Island - Buchanan, Ruth; Hewitt, Jeffery G. (Osgoode Digital Commons, 2017)
The eighteenth and nineteenth centuries generated a trove of objects documenting the encounter between the Anishinaabe of the Great Lakes region and the British. Two such objects, a drum painted with Anishinaabe imagery and a treaty, handwritten by a British treaty commissioner, were created in close proximity in both time and location. This paper explores the encounter between the Anishinaabe and the British through a parallel engagement with both drum and treaty; placing them in conversation with each other. We consider the divergent paths taken by these objects by comparing the material, legal and sensory landscapes in which they were produced with their current contexts. In dialogue, the objects reveal their performative contributions to the British imperial project; one as an authorised claim to (indigenous) property, the other as (British Museum) property, displayed as artefact. Read in parallel, the treaty’s assertions of authority and the drum’s mute resistance interrogate the form of law itself, and the agency of law’s objects.